RESPONS BAWANG MERAH TERHADAP PEMUPUKAN ORGANIK DI LAHAN KERING (Respond of Onion to Organic Fertilizer in Dry Land) - I Nyoman Adijaya (Widyariset, 2010)
Onion demand in Bali is supplied from other provinces in about 40%, therefore onion is one of prospective commodity to be developed in Bali. An assessment on respond of onion to organic fertilizer was done in Sanggalangit Village, Gerokgak District, Buleleng Regency of Bali Province from July to September 2008. The trial was designed using Randomized Complete Block Design with 5 replications. Fertilization treatments tested were RB 10 t ha-1, cow urine 15,000 l ha-1, combination of RB 5 t ha-1 + cow urine 7,500 l ha-1, and without fertilizer as control. Organic fertilizer could improve physical character of the soil in term of decrease bulk density from 1,149 g cm-3 to 1.111 g cm-3–1.085 g cm-3 and improve growth and yield of onion. Onion yield significantly increased 32.71%–60.77% compared to control. Utilization of organic fertilizer, RB and cow urine, which will applied either singly or combination can improve physical character of the soil and increase the yield of onion.